4 - How Britain Underdeveloped Bechuanaland Protectorate: A Brief Critique of the Political Economy of Colonial Botswana: DOI: 10.4314/ad.v31i1.22251 - Mogalakwe, Monageng (Africa Development, 2006)
Britain declared Bechuanaland a ‘protectorate’ in 1885 in a move largely driven by military strategic considerations rather than by the availability of economic resources. This can give the impression that in Botswana the process of eco- nomic underdevelopment, that is often associated with colonialism, never took place in this British ‘protectorate’. This article reveals that even in the so-called ‘protectorate’, the British colonial state policies subverted indigenous economic interests and stifled opportunities for indigenous private capital accumulation, while actively promoting the economic interests of a small white settler capitalist class.